Previous obstetrical history does not impact short-term mid-urethral sling outcomes - Ole Aleksander Dyrkorn; Anne Cathrine Staff; Sigurd Kulseng-Hanssen; Rune Svenningsen (Norsk Forening for Epidemiologi, 2023)
The following paper is reprinted from the International Urogynecology Journal International Urogynecology Journal (2021) 32:1733-1743 https://doi.org/10.1007/s00192-021-04836-5